2020
DOI: 10.1186/s40580-019-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

Tunable metasurfaces for visible and SWIR applications

Abstract: Demand on optical or photonic applications in the visible or short-wavelength infrared (SWIR) spectra, such as vision, virtual or augmented displays, imaging, spectroscopy, remote sensing (LIDAR), chemical reaction sensing, microscopy, and photonic integrated circuits, has envisaged new type of subwavelength-featured materials and devices for controlling electromagnetic waves. The study on metasurfaces, of which the thickness is either comparable to or smaller than the wavelength of the considered incoming ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…In order to fully utilize this optical activity, using plasmonic materials with inherently strong light-matter interactions for the construction of chiral nanomaterials has been highlighted. [1][2][3][4][5][6][7] Considering that chiral plasmonic nanostructures with various shapes and physical dimensions offer versatility to the chiroptic response, a synthetic platform for the sophisticated control of nanoscale chirality is required. Given that the shape and physical dimensions of chiral plasmonic nanostructures play a critical role in obtaining a desired optical response, precise control over the size and morphology of a chiral plasmonic nanomaterial using various artificial synthesis methods has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…In order to fully utilize this optical activity, using plasmonic materials with inherently strong light-matter interactions for the construction of chiral nanomaterials has been highlighted. [1][2][3][4][5][6][7] Considering that chiral plasmonic nanostructures with various shapes and physical dimensions offer versatility to the chiroptic response, a synthetic platform for the sophisticated control of nanoscale chirality is required. Given that the shape and physical dimensions of chiral plasmonic nanostructures play a critical role in obtaining a desired optical response, precise control over the size and morphology of a chiral plasmonic nanomaterial using various artificial synthesis methods has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…By now, metasurfaces have been used to demonstrate both typical and exotic optical behavior with improved quality regarding dispersion [ 17 , 18 , 19 ], and tuning range [ 20 , 21 ]. The set of so-called exotic materials and associated properties includes non-local response metasurfaces [ 22 ], anomalous reflection and refraction structures [ 7 , 23 ], optical cloaking [ 24 , 25 ], frequency-selective surfaces [ 20 , 26 ] offering the potential of giant magnetic resistance [ 27 ], epsilon near-zero metasurfaces [ 28 , 29 ], hyperbolic metasurfaces [ 30 , 31 , 32 ], and generalized Kerker-effect structures [ 33 , 34 ]. In construction of the so-called meta-atoms, metallic structures of either gold, silver, or copper were initially deposited on a dielectric substrate, changing the phase structure of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, similar schemes were also employed for active control in silicon photonics by integrating active materials (e.g., graphene [ 59 , 60 , 61 ] or PCM [ 62 , 63 , 64 , 65 ]) into integrated photonic devices. Due to their prospects in micro and nanophotonics, a few review papers were recently reported on both on-chip based active photonic devices [ 65 , 66 , 67 , 68 , 69 ] and tunable metasurfaces [ 48 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Introductionmentioning
confidence: 99%